Creation and Ecology: A Hermeneutical Analysis of GEN 1:26 and 28 (Hekima Review, 2015)
“Then God said: let us make human beings in our image, after our likeness. Let them have dominion over the fish of the sea, the birds of the air, the tame animals, and all the creatures that crawl on the earth. God blessed them and said to them: Be fertile and multiply; fill the earth and subdue it. Have dominion over the fish of the sea, the birds of the air, and all the living things that crawl on the earth.” Gen1:26 and 28.